Patients’ and psychiatrists’ stance on the current state of pharmacological depression treatment in Serbia and prospects of introduction of personalized pharmacotherapy and its potential effects - Jeremić, Aleksandra; Milosavljević, Filip; Opanković, Ana; Jukić, Marin (Archives of Pharmacy, 2022)
The use of antidepressants has been steadily increasing. Even though the amount of evidence on the usefulness of personalized drug dosing in depression treatment is growing, there is still resistance and skepticism among physicians and regulators regarding the implementation of CYP450 genotyping and therapeutic drug monitoring in psychiatric clinical practice. The aim of this study was to quantify the opinions of psychiatrists and patients from three large psychiatric clinics in Belgrade, Serbia, and to examine what requirements need to be met to make changes in clinical guidelines or recommendations. All participants completed an anonymous questionnaire that was developed at the Faculty of Pharmacy, University of Belgrade. Fourteen practicing psychiatrists and 30 patients currently treated for depression completed the questionnaire. Distributions of opinion scores were compared between the psychiatrists and patients upon the visual inspection of the violin plots. Our results show that psychiatrists predominantly have a positive opinion on personalized dosing in psychiatry and that patients are most likely to comply with new approaches in depression pharmacotherapy. However, due to the long time needed for regulatory change, it is very unlikely that personalized dosing would be rapidly implemented in clinical practice, even if adequate evidence was to emerge.
Keywords: major depressive disorder; precise medicine; therapeutic drug monitoring; Pharmacogenetics